CytoSorb® Hemoadsorption as a Promising Tool to Handle COVID-19-Induced Cytokine Storm - Alice-Christin Acevedo; Michael Zoller; Christina Scharf; Uwe Liebchen; Michael Irlbeck; Ines Schroeder (Case Reports in Critical Care)
Accumulating evidence suggests that a patient subgroup with severe COVID-19 develops a cytokine release syndrome leading to capillary leakage and organ injury. Recent publications addressing therapy of cytokine storms recommended new extracorporeal therapies such as hemoadsorption. This case report describes a 59-year-old SARS-CoV-2-positive patient with severe ARDS. Due to severe hyperinflammation with concomitant hemodynamic instability and progressive renal failure, combination of continuous renal replacement and CytoSorb® hemoadsorption therapy was initiated. Treatment resulted immediately in a control of the hyperinflammatory response. Simultaneously, lung function continued to improve accompanied by profound hemodynamic stabilization. We report the successful utilization of CytoSorb® hemoadsorption in the treatment of a patient with SARS-CoV-2-induced cytokine storm syndrome.